A qualification procedure to manufacture and repair aerospace parts with electron beam melting. (October 2016) - Portolés, L.; Jordá, O.; Jordá, L.; Uriondo, A.; Esperon-Miguez, M.; Perinpanayagam, S.
Abstract: This paper is focused on qualification procedures for metal parts manufactured using new additive manufacturing (AM) techniques in the aerospace industry. The main aim is to understand the interaction between these technologies and the stringent regulatory framework of this industry in order to develop correct quality assurance and quality control procedures in accordance with the certification process for the technology and spare parts. These include all the testing and validation necessary to implement them, as well as to maintain their capability throughout their life-cycle, specific procedures to manufacture or repair parts, work-flows and records, amongst others. An entire qualification procedure for electron beam melting (EBM) to reproduce and repair an aerospace part has been developed and it is presented in this paper. These will be part of the future quality assurance and quality management systems of those aerospace companies that implement AM in their supply chain.